MECHANISM FOR HANDLING CASES OF GENERAL CRIMINAL ACTS OF VIOLENT THEFT BY PROSECUTORS IN BATAM STATE PROSECUTORS - Thiara Dewi Purnama; Rahmi Ayunda (ConCEPt - Conference on Community Engagement Project, 2022)
The crime of violent theft is the act of a person to injure the victim with the aim that the goods taken remain in the victim's power. Batam State Prosecutor is an agency engaged in law enforcement under the mandate of the "Prosecutorof the Republic of Indonesia" which gives orders and authorities in responding to prosecutions, implementing court rulings, and other authorities. The purpose of this writing will be to understand the role of prosecutors in handling cases of "violenttheft study number: 578 / Pid.B / 2021 / PN" Btm. The author uses primair data and secondary data with observation and interview methods in conducting this study. Prosecutors are guided by standard operating procedures (SOP) "Attorney GeneralRegulation No: PER-036-A / JA / 09/11" in accordance with positive law applicable in Indonesia in examining the case file of common criminal acts, especially violent theft.